Gandhāran art in its Buddhist context : papers from the Fifth International Workshop of the Gandhāra Connections Project, University of Oxford, 21st-23rd March, 2022 - Rienjang, Wannaporn; Stewart, Peter, 1971- (Archaeopress Archaeology, 2023)
This edited volume considers Gandharan art in relation to its religious contexts and meanings within ancient Buddhism. Addressing the responses of patrons and worshippers at the monasteries and shrines of Gandhara, papers seek to understand more about why Gandharan art was made and what its iconographical repertoire meant to ancient viewers.